Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity (EOQ) Pada Home Industry Tahu Di Aceh Tamiang - Safrizal, Safrizal; Fadhilah, Fadhilah; Rahman, Maulana (Movere Journal, 2024)
Inventory management of raw materials is a significant form of control that profoundly influences the production process. Surplus or shortage of raw materials can potentially hinder production processes. One of the methods used in analyzing raw material inventory is the Economic Order Quantity (EOQ) method in tofu home industries in Aceh Tamiang. The EOQ method is employed to optimize the order quantity and inventory costs, considering holding and ordering costs. This research also analyzes safety stock, reorder point, total inventory cost, and just-in-time principles applied to produce goods according to consumer demand. The results of this study indicate that in 2023, the tofu home industry made raw material purchases when inventory levels reached a point of 515.45 kg. The company's lead time for raw material ordering is 2 days, with a calculated safety stock of soybeans amounting to 219.45 kg. Significant cost savings were achieved, as evidenced by a total cost calculation of Rp. 556,866, which is much lower than the total inventory cost of Rp. 1,716,880. By implementing EOQ, tofu home industries can enhance operational efficiency and optimize resource utilization. The practical implication of this research is that the use of the EOQ method can contribute to improving profitability and sustaining tofu home industries in Aceh Tamiang.